PECULIARITIES OF ADULT ATOPIC DERMATITIS AND ECZEMA COURSE - Aleksandruk, O. D.; Senyshyn, N. Y. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
With regards to big number of atopic dermatitis end eczema patients we performed analysis of medical history and clinical signs of adult atopic dermatitis and true eczema patients under the in-patient treatment and at early follow-up period. Common and different features of medical and personal history were shown. Effectiveness of in-patient treatment and lesions dynamics under out-patient treatment were estimated. Majority of patients have signs of the disease at discharge. Part of the patients have signs of worsening during 1 months of follow-up. One third of the patients only are expected to cooperate with medical staff in effective manner due to special way of disease cooping.